Evaluating effects of physical soil and water conservation measures using farmers' perception and soil analysis in southern Ethiopia - Ermias, H.; Wolka, K.; Biazin, B. (Commonwealth Scientific and Industrial Research Organisation, 2024)
Context Soil and water conservation (SWC) measures have been widely practiced on cultivated lands across regions but evidence on their effects is inadequate. Aims To examine the effects of variously aged SWC measures on cultivated land. Methods A total of 122 farm households were interviewed. At the 0-20 cm layer, soil samples (n = 59) were collected from soil bunds of <5 years, 5-10 years, and 10-15 years old, and no-bund adjacent fields and analysed in the laboratory. Key results Approximately 40% of respondents perceived soil erosion as a severe problem in their area. The respondents (70%) practiced the introduced SWC measures such as soil bunds. The introduced SWC measures are beneficial in improving soil fertility (78%) and thus 96% of the respondents were interested in repairing and sustaining it. The soil pH, soil organic carbon, total nitrogen, and available phosphorous were significantly (P < 0.05) greater in the fields with bunds of 10-15 years old than the fields with bunds of less than 10 years. The 10-15 year old bund showed greater soil organic carbon (37%), total nitrogen (40%), and available phosphorous (27%) than adjacent no-bund fields, implying that SWC can show effects on soil in the long term. Conclusions The results of the study revealed that the effects of physical SWC measures on soil properties can be observed after a decade of managing them. Implications Farmers are advised to repair and retain bunds if the erosion-prone areas are used for cultivating annual crop.